Civil Registration, Legal Reforms, Public Health, and SDG 16.9: Catalyzing Social Inclusion for Transgender Persons in India - Bera, Om Prakash; Shah, Vandana; Chandge, Mokshada; Singh, Ranjit; Singh, Arshdeep; Kumari, Lalita; Shrama, Shuchi (Indian Journal of Community Health, 2025)
Civil registration is a crucial process for documenting vital life events such as births, deaths, and marriages, which form the foundation of an individual's legal identity. For transgender persons in India, this process has historically been fraught with challenges, including systemic discrimination, bureaucratic hurdles, and a lack of inclusive legal frameworks. This paper examines the evolving landscape of civil registration for transgender individuals, focusing on legislative measures like the Transgender Persons (Protection of Rights) Act, 2019, and 2023 amendment to the Registration of Births and Deaths Act, 1969. By analysing key judicial interventions, such as the NALSA judgment of 2014, and exploring international best practices, this study identifies gaps and proposes actionable recommendations to enhance inclusivity. It highlights the importance of simplifying procedures, raising awareness, and protecting data privacy to ensure that transgender persons can access their right to civil registration without discrimination. The findings underscore the critical role of legal recognition in fostering equality, dignity, and social inclusion for transgender individuals in India.